(untitled) (International Association of Biologicals and Computational Digest, 2022)
Sesamum indicum is an important food oil crop of India. It is useful in many aspects like seeds for oil, seed cake (after oil extraction) as fodder, Seeds as one of the richest sources of calcium carrying many nutrients, seeds having therapeutic properties along with many cosmetic uses. For releasing any new variety of crop DUS (Distinctness, Uniformity and Stability) Test is done. For conducting DUS Test many morphological characteristics are observed for several generations and uniformity stability of characteristics are noted down. We observed morphological characteristics of 16 Sesamum crop varieties from different regions of India for DUS Testing. Result shown that even geographically different Sesamum crop can be grouped into one. So, along with morphological characteristics, Biochemical and Molecular markers are also suggested to be included for DUS Testing.